Analysis Of Economic Growth Levels: Literature Study Of International Graphics Of Indonesian Export And Import Value - Salsabila, Salsabila; Noer, Muhammad Raihan; Matondang, Khairani Alawiyah (Jurnal Ekonomi Balance, 2024)
Analysis of the level of economic growth through a literature study of graphs of export and import values aims to find out whether movements in export and import graphs have an influence and are relevant to the level of economic growth in Indonesia. The time period used in the research was 10 years, namely from 2010 to 2020. The method for collecting data used secondary methods by obtaining data through the Central Statistics Agency (BPS) and journal literature or previous research. Data analysis is explained descriptively through each graphic sample, namely; 1) Economic Growth Rate, 2) Indonesian Export Value 3) Indonesian Import Value. This research produces explanations in the form of; 1) Indonesia's economic growth rate experiences fluctuations which tend to decrease. 2) The level of Indonesian export value experiences fluctuations which tends to decrease. 3) Indonesia's import level experiences increasing fluctuations which leads to the conclusion that state spending is greater. Researchers suggest that the government as the party with the authority be able to make policies to maximize state income through exports and minimize imports of foreign goods.